Chemical Composition and Antimicrobial Activity of the Volatile Oil of Salvia santolinifolia Boiss. From Southeast of Iran - Mir Babak Bahadori, Hassan Valizadeh , Mahdi Moridi Farimani (Tabriz University of Medical Sciences, 2016)
Background: Salvia santolinifolia is a medicinal plant, traditionally used for the treatment of inflammation, hypercholesterolemia, hemorrhoids and diarrhea. Discovery of new natural antimicrobial agents is necessary because of microorganism's resistance to common antibiotics. Methods: Essential oil of S. santolinifolia was analyzed by GC-FID and GC-MS. Antibacterial, antifungal and general toxic activities of the essential oil were also evaluated. Results: Chemical analysis of the oil revealed that α-pinene (49.3%), β-eudesmol (20.0%), camphene (7.8%) and limonene (7.7%) are the major components of the essential oil of S. santolinifolia. The inhibition zones ranged from 11.5 to 23.8 mm. Minimum inhibitory concentrations of the oil obtained from 200 to 800 µg/ml against several microbial strains. Conclusion: Our results showed that the volatile oil of S. santolinifolia could be considered as a rich source of natural agents for several uses as antibiotics against human pathogenic microbes.